PREDICTION OF WAVE RUN-UP ON A COASTAL IMPERMEABLE STRUCTURE - Mustafid .; Slamet Hargono; Wicakcono, Bambang Rizki (JOURNAL OF COASTAL DEVELOPMENT, 2001)
A knowledge of wave run-up behavior on a coastal structure is one of the most important factors affecting the design of coastal structures exposed to wave attack. Prediction of wave run-up on a coastal impermeable structure with slope face and various friction factors are discussed with simplifying assumptions. An analytical approach is given for predicting wave run-up based on data measurements as the parameters of incident waves entering to coastal structure. Statistical approach with Weibull distribution is given on prediction of wave run-up, and present the probability distribution of wave run-up height.